Student Character Development Based On The 2013 Curriculum - Wiwik Maladerita; Vini Wela Septiana; Mega Iswari (CV. AFDIFAL MAJU BERKAH, 2022)
This paper examines the students character development based on the 2013 curriculum in SDN 05 Alang Rambah. This research is a type of qualitative research with the research subject of State Elementary School (SDN) 05 Alang Rambah. In this study, it can be concluded that how that the Reality of Character Education of Students Based on the 2013 Curriculum of State Elementary School (SDN) 05 Alang Rambah and teachers have used various strategies and patterns in instilling Character Education for Students of State Elementary School (SDN) 05 Alang Rambah. Based on these results, it can be said that teachers have implemented character development for students based on the 2013 curriculum at State Elementary School (SDN) 05 Alang Rambah.